2015
DOI: 10.1155/2015/406327
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Medical Monitoring System for Heart Failure Prognosis

Abstract: Remote monitoring of heart disease provides the means to keep patients under continuous supervision. In this paper, we introduce the design and implementation of a remote monitoring medical system for heart failure prediction and management. The three-part system includes a patient-end for data collection, a medical data center as data storage and analysis, and a doctor-end to diagnosis and intervention. The main objective of the system is to prognose the occurrence risk of heart failure (HF) confirmed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Ten of the 18 studies included in this review had small sample sizes of 40 or fewer participants (8 studies assessed usability of the mobile system for refinement or further development of an algorithm [31-40]), 4 studies had sample sizes of 41 to 99 [41-44], and 4 studies had 100 or more participants (but fewer than 200) [45-48]. Four of the 18 studies reviewed were pilot RCTs [32,34,42,44], and only 2 RCTs had 100 or more participants [47,48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of the 18 studies included in this review had small sample sizes of 40 or fewer participants (8 studies assessed usability of the mobile system for refinement or further development of an algorithm [31-40]), 4 studies had sample sizes of 41 to 99 [41-44], and 4 studies had 100 or more participants (but fewer than 200) [45-48]. Four of the 18 studies reviewed were pilot RCTs [32,34,42,44], and only 2 RCTs had 100 or more participants [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…All 18 studies used mHealth technology via mobile phones or tablets as the medium for self-care intervention. A total of 11 studies reported outcome data (Table 1), 7 studies reported only usability of the mobile technology (Table 2), and 1 study developed an algorithm to differentiate HF but did not provide usability or efficacy data [40].…”
Section: Resultsmentioning
confidence: 99%
“…It enables storing large data sets for heart rate, stress, and Require: newSample of HR Ensure: Identification of abnormality events (1) if newSample is normalRead then (2) staAbnormality is false (3) if staAbnormality is true then (4) if sampleTime − staAbnTim > gapTime then (5) Abnormal Episode (6) else (7) newSample (8) end if (9) else (10) staAbnormality es true (11) staAbnTim it is equal to sampleTime (12) end if (13) end if ALGORITHM 1: Identification of AHREs. Mobile Information Systemslocation monitoring services, which can be accessed when required.…”
Section: Phase 2: Cma-hr-sl Functions For Storing Data In the Cloudmentioning
confidence: 99%
“…e web platform was developed to browse through the stored information so that caregivers can have access to Require: Data to be monitored I � GPS, HR, SL { } not empty Ensure: Identification of abnormality episodes (1) while I ≠ null do (2) if connection BLE is true then (3) CMA-HR-SL receives I and executes anomaly identification algorithm (4) else (5) connection BLE is false (6) end if (7) Establish WiFi connection and send I to external storage service (8) External storage service provides I to web platform (9) Carer visualizes episodes of abnormality of the patient from web platform (10) end while ALGORITHM 2: Monitoring and location process.…”
Section: Phase 3: Cma-hr-sl Support For Caregiversmentioning
confidence: 99%
See 1 more Smart Citation